Students' mathematical lateral thinking skills in creative problem-solving - Yusmin, Edy; Yani T, Ahmad; Pasaribu, Revi Lestari; Fitriawan, Dona (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
This study aimed to examine students' mathematical lateral thinking skills in creative problem-solving, differences in subjects' answers based on the level of their study period, and factors that affect students' lateral thinking skills. The descriptive method was used in the form of an educational survey. The sampling technique used in this research was stratified random sampling. The research subjects were first, third, and fifth-semester students of Mathematics Education at FKIP Tanjungpura University in 2019. The data collection technique used was the "Paper-and-pencil Assessment," with the written test sheet adopted from the Mathematical Lateral Logic Test by Bruce Woodcock. The results showed that students' lateral mathematical thinking skills in creative problem-solving were in the poor category, with an average score of 9.39 out of 25. The results of statistical tests with a value of χ2 indicated that the answers to the subjects were different based on the level of study. The ability to recognize dominant ideas and the polarization of perception of the problem, and the ability to use other ideas are the dominant factors affecting the level of students' mathematical lateral thinking skills in all subject groups. In general, the way of thinking with formal logic or thinking vertically affected students' lateral thinking patterns.